1985
DOI: 10.1111/j.1469-8137.1985.tb02837.x
|View full text |Cite
|
Sign up to set email alerts
|

DIFFERENTIAL TOLERANCE OF THREE CULTIVARS OF AGROSTIS CAPILLARIS L. TO CADMIUM, COPPER, LEAD, NICKEL AND ZINC

Abstract: SUMMARYRoot growth of seedlings of the Agrostis capillaris L. cultvars Parys (copper tolerant), Goginan (lead/zinc tolerant), and Highland (non tolerant) was measured after 14 d growth in solution cultures with increasing concentrations of Cd, Cu, Pb, Ni and Zn.Increasing inhibition of root growth of all three cultivars occurred with increasing concentrations of all five metals. Highland being most affected. In Cu, Parys was least affected; in Pb and Zn Goginan was least affected. Parys and Goginan thus displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 20 publications
2
47
0
Order By: Relevance
“…It might be expected that there would be a 'cost' incurred by tolerance to high NaCI, manifest as reduced growth compared with unselected material in the absence of NaCI (as is shown by some species in populations tolerant to heavy metals; Symeonidis, McNeilly & Bradshaw, 1985). Not only has this not occurred, but the reverse pattern was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be expected that there would be a 'cost' incurred by tolerance to high NaCI, manifest as reduced growth compared with unselected material in the absence of NaCI (as is shown by some species in populations tolerant to heavy metals; Symeonidis, McNeilly & Bradshaw, 1985). Not only has this not occurred, but the reverse pattern was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Root length is a character which has been successfully used for screening grass species for heavy metal tolerance (Symeonidis, McNeilly & Bradshaw, 1985) and has also been recommended as a selection criterion for salt tolerance (Hannon & Bradshaw, 1968;Khan & Marshall, 1981;Wu, 1981). Recently, however, Rozema & Visser (1981) have questioned whether root length is a suitable criterion in selection, and they suggest that it is not a successful measure of salt tolerance in Festuca rubra L. Tiku & Snaydon (1971) reached the same conclusion for Agrostis stolonifera L.…”
Section: Introductionmentioning
confidence: 99%
“…However, the other mines, whose soil contains less cadmium than the maximum permitted in agricultural soils (= 2.0 ig g1, SAOMC, 1992), also have much higher tolerance to this metal than the Symeonidis at al., 1985). However, a nonmine population from the same area, CL4O, which was not copper tolerant, was also far more cadmium tolerant than the isogenic lines (Fig.…”
Section: Sh4mentioning
confidence: 99%
“…445 cadmium cotolerance in higher plants using five populations of Silene vulgaris (Moench) Garcke. Symeonidis et al (1985) showed that copper-tolerant populations of A. capillaris also had elevated levels of tolerance to other heavy metals, including cadmium. Allen & Sheppard (1971) observed that the highly copper-tolerant population of Mimulus guttatus Fischer cx DC from the Copperopolis mine also had a high mean tolerance to zinc, lead and nickel, even though these metals were not present substantially in the soil from this mine, and suggested that metal tolerance in this species was general to many heavy metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation